2020
DOI: 10.1039/d0cc04413j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and hetero-Diels–Alder reactions of enantiomerically pure dihydro-1H-azepines

Abstract: Thermolysis of enantiomerically pure 3-substituted 7,7-dihalo-2-azabicyclo[4.1.0]heptanes in the presence of K2CO3 gives in good yields 2-alkyl-6-halo-1-tosyl-2,3-dihydro-1H-azepines. These undergo highly stereoselective [4+2] cycloaddition reactions with heterodienophiles and arylation/alkenylation under Suzuki conditions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 41 publications
0
27
0
Order By: Relevance
“…The other diastereoisomer exo - 11 had been left unreacted under the same conditions, which is consistent with the Woodward–Hoffmann–DePuy rule. 1 a The production of 12 can readily be interpreted as the result of the loss of a proton from the iminium intermediate 13 , 13 rather than the desired cyclisation to the tricyclic system 14 .…”
Section: Resultsmentioning
confidence: 99%
“…The other diastereoisomer exo - 11 had been left unreacted under the same conditions, which is consistent with the Woodward–Hoffmann–DePuy rule. 1 a The production of 12 can readily be interpreted as the result of the loss of a proton from the iminium intermediate 13 , 13 rather than the desired cyclisation to the tricyclic system 14 .…”
Section: Resultsmentioning
confidence: 99%
“…To further expand the scope of dienophiles in the cycloaddition of azepino[4,5‐ b ]indoles, 4‐phenyl‐3 H ‐1,2,4‐triazole‐3,5(4 H )‐dione (PTAD), a reactive dienophile was used to perform the hetero‐Diels‐Alder reaction [11,16] . It was found that all the reactions underwent smoothly with no catalyst, affording the endocyclic hetero‐Diels‐Alder cycloaddition products in high yields (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…reaction. [11,16] It was found that all the reactions underwent smoothly with no catalyst, affording the endocyclic hetero-Diels-Alder cycloaddition products in high yields (Table 4). [17] This result implied that the occurance of retro-aza-Michael reaction could be tuned by changing the type of the dienophiles.…”
Section: Ac)mentioning
confidence: 99%
See 2 more Smart Citations